Tính \(\sqrt{1}-\sqrt{4}+\sqrt{9}-\sqrt{16}+\sqrt{25}-\sqrt{36}+.....-\sqrt{400}\)
Tính: \(\sqrt{1}\) - \(\sqrt{4}\) + \(\sqrt{9}\) - \(\sqrt{16}\) + \(\sqrt{25}\) - \(\sqrt{36}\) +..............- \(\sqrt{400}\)
(Giải nhanh nhé,gấp lắm)
=1-2+3-4+5-6+...+19-20
=-1-1-1-1-1-1-...-1
20 so-1
=-1.20=-20
\(\sqrt{1}\) - \(\sqrt{4}\) + \(\sqrt{9}\) - \(\sqrt{16}\)+ \(\sqrt{25}\)- \(\sqrt{36}\)+ ... - \(\sqrt{400}\)
5\(\sqrt{16}\)-4\(\sqrt{9}\)+\(\sqrt{25}\)-0,3\(\sqrt{400}\)
E = \(5\sqrt{16}-4\sqrt{9}+\sqrt{25}-0,3\sqrt{400}\)
a,\(\sqrt{1}+\sqrt{9}+\sqrt{25}+\sqrt{49}+\sqrt{81}\) c\(\sqrt{0,04}+\sqrt{0,09}+\sqrt{0,16}\)
b,\(\sqrt{\dfrac{1}{4}}+\sqrt{\dfrac{1}{9}}+\sqrt{\dfrac{1}{36}}+\sqrt{\dfrac{1}{16}}\) e\(\sqrt{2^2}+\sqrt{4^2}+\sqrt{\left(-6^2\right)}+\sqrt{\left(-8^2\right)}\)
j,\(\sqrt{1,44}-\sqrt{1,69}+\sqrt{1,96}\)
g, \(\sqrt{\dfrac{4}{25}}+\sqrt{\dfrac{25}{4}}+\sqrt{\dfrac{81}{100}}+\sqrt{\dfrac{9}{16}}\)
d\(\sqrt{81}-\sqrt{64}+\sqrt{49}\)
a)\(\sqrt{1}\)+\(\sqrt{9}\)+\(\sqrt{25}\)+\(\sqrt{49}\)+\(\sqrt{81}\)
=1+3+5+7+9
=25
b)=\(\dfrac{1}{2}\)+\(\dfrac{1}{3}\)+\(\dfrac{1}{6}\)+\(\dfrac{1}{4}\)
=\(\dfrac{6}{12}\)+\(\dfrac{4}{12}\)+\(\dfrac{2}{12}\)+\(\dfrac{3}{12}\)
=\(\dfrac{15}{12}\)
c) =0,2+0.3+0,4
= 0.9
d) =9-8+7
=8
j) =1,2-1,3+1.4
= (-0,1)+1,4
=1,4
g) \(\dfrac{2}{5}\)+\(\dfrac{5}{2}\)+\(\dfrac{9}{10}\)+\(\dfrac{3}{4}\)
= (\(\dfrac{4}{10}\)+\(\dfrac{15}{10}\)+\(\dfrac{9}{10}\))+\(\dfrac{3}{4}\)
= \(\dfrac{14}{5}\)+\(\dfrac{3}{4}\)
=\(\dfrac{56}{20}\)+\(\dfrac{15}{20}\)
= \(\dfrac{71}{20}\)
Nhớ tick cho mk nha~
\(5\sqrt{16}-4\sqrt{9}+\sqrt{25}-\sqrt{400}\)
\(5\sqrt{16}-4\sqrt{9}+\sqrt{25}-\sqrt{400}\)
\(=5.4-4.3+5-20\)
\(=20-12+5-20\)
\(=-7\)
5√16−4√9+√25−√400
=5.4−4.3+5−20
=20−12+5−20
=8+5-20
=13-20
=-7
\(5\sqrt{16}-4\sqrt{9}+\sqrt{25}-0,3\sqrt{400}\)
\(5\sqrt{16}-4\sqrt{9}-\sqrt{25}-0,3\sqrt{400}\)
\(=5.4-4.3+5-0,3.20\)
\(=20-12+5-6\)
\(=7\)
\(5\sqrt{16}-4\sqrt{9}+\sqrt{25}-0,3\sqrt{400}\)
\(5.\sqrt{16}-4.\sqrt{9}+\sqrt{25}-0,3.\sqrt{400}\)
\(=5.4-4.3+5-\frac{3}{10}.20\)
\(=20-12+5-6\)
\(=8+5-6\)
\(=13-6\)
\(=7\)
=5*4-4*3+5-0.3*20
=20-12+5-6
=8+5-6
=13-6
=7
a) \(\dfrac{2}{5}\sqrt{25}\) -\(\dfrac{1}{2}\sqrt{4}\) b)0,5\(\sqrt{0,09}\) +5\(\sqrt{0,81}\) c)\(\dfrac{2}{5}\sqrt{\dfrac{25}{36}}\) -\(\dfrac{5}{2}\sqrt{\dfrac{4}{25}}\)
d)-2\(\sqrt{\dfrac{-36}{-16}}\) + 5\(\sqrt{\dfrac{-81}{-25}}\)
`#3107.101107`
a)
`2/5 \sqrt{25} - 1/2 \sqrt{4}`
`= 2/5 * \sqrt{5^2} - 1/2 * \sqrt{2^2}`
`= 2/5*5 - 1/2*2`
`= 2 - 1`
`= 1`
b)
`0,5*\sqrt{0,09} + 5*\sqrt{0,81}`
`= 0,5*\sqrt{(0,3)^2} + 5*\sqrt{(0,9)^2}`
`= 0,5*0,3 + 5*0,9`
`= 0,15 + 4,5`
`= 4,65`
c)
`2/5\sqrt{25/36} - 5/2\sqrt{4/25}`
`= 2/5*\sqrt{(5^2)/(6^2)} - 5/2*\sqrt{(2^2)/(5^2)}`
`= 2/5*5/6 - 5/2*2/5`
`= 1/3 - 1`
`= -2/3`
d)
`-2 \sqrt{(-36)/(-16)} + 5 \sqrt{(-81)/(-25)}`
`= -2*\sqrt{36/16} + 5*\sqrt{81/25}`
`= -2*\sqrt{(6^2)/(4^2)} + 5*\sqrt{(9^2)/(5^2)}`
`= -2*6/4 + 5*9/5`
`= -3 + 9`
`= 6`